KEKUATAN EKONOMI INDONESIA ‎ DI TENGAH KEKUATAN EKONOMI GLOBAL - Erni Setiawati; Yofy Gresyla Lestari (Economic Faculty, University of Widya Gama Mahakam Samarinda, 2022)
Indonesia's Economic Strength in the Middle of Global Economic Strength. Indonesia is ranked 16th with a GDP of US 1.2 trillion or 1.2% of world (global) GDP. Based on the summary of data from the International Monetary Fund (IMF), referring to the prediction of the amount of Gross Domestic Product (GDP) of each country, Indonesia is included in 4 (four) Asian countries as the top five ranks which will begin to dominate global economic power. In the infographic included with the title “Continental Shift: The World's Largest Economy of All Time”, there are about 11 names of countries from four continents, including Indonesia representing Asia along with China, Japan and India. In 2011, as the world population map changes, it is predicted that Indonesia will get a demographic bonus where the population of Indonesia will be dominated by the productive age group, so that it will be ranked as the 12th world economic power. The research was carried out by the international team in the journal The Lancet (2020) under the title Fertility, mortality, migration, and population scenarios for 195 countries and territories from ‎2017 to 2100: forecasting analysis for the Study of the Global Burden of Disease. The study noted that Indonesia will be in the 12th position in the world starting in 2050, meaning 30 years from now. Meanwhile, in 2030, it will rank 14th in the world economy. ️ Indonesia is the only ASEAN country that is a member of the G-20 (or the 20 Group). The countries in this group consist of 19 countries plus the European Union; controls 75% of world trade. The G20 is a collection of countries with the largest economic power in the world. Currently, Indonesia's position is 16th based on the world's largest GDP or Gross Domestic Product (GDP). The magnitude of this has resulted in Indonesia being now included in the association of 20 large countries that have a